Footprint of a large intracontinental rifting event: Coupled detrital zircon geochronology and geochemistry from the Mesoproterozoic Collier Basin, Western Australia - Armandola, S.; Barham, Milo; Reddy, Steven; Clark, Christopher; Spinks, S. (Elsevier BV, 2018)
Intracontinental rifting of the Capricorn Orogen was accompanied by the emplacement of mafic intrusions at c. 1080 Ma, contemporaneous with deposition of siliciclastic and volcanoclastic sediment in the late Mesoproterozoic Collier Basin. In this work we investigate the provenance of the Collier Basin sediment with U-Pb and trace elements data for detrital zircons. Visual inspection of age data signature and statistical Kolmogorov-Smirnov similarity test integrated with trace element analysis of detrital zircon suggest that the Collier Basin contains two distinct sequences, in terms of sedimentary provenance and depositional history. The basal units of the Collier Basin were deposited in a deltaic setting, and are dominated by early to middle Palaeoproterozoic detrital zircon ages matching older sedimentary rocks on the south margin of the Pilbara Craton (Ashburton and Capricorn Groups), and underlying Mesoproterozoic sedimentary sequences in the central Capricorn Orogen (Edmund Basin). The topmost sequence of the Collier Basin contains unimodal late Mesoproterozoic detrital zircon populations (1300–1100 Ma) interpreted to be associated with the Musgrave Province from central Australia, ~1000 km distant. The sediment transport of the topmost unit occurred via marine conduit in a rift environment, with its axis elongated from southeast to northwest. The data indicate that rifting within the Capricorn Orogen is linked with the 1090–1040 Ma intracontinental Ngaanyatjarra Rift of central Australia, which is interpreted to have facilitated dispersal of Musgrave Province detritus between Western Australia and central Australia.